LncRNA DCST1-AS1 drives the malignant progression of pediatric acute myeloid leukemia via regulating p53 methylation: LncRNA DCST1-AS1 and pediatric AML - Wang, Jian; Li, Yan; Xu, Zhe; Wang, Min; Cheng, Jie; Gao, Shan; Kong, Weiyu; Qu, Lijun (Cellular and Molecular Biology, 2023)
To uncover the biological role of lncRNA DCST1-AS1 in the process of pediatric AML and its regulatory effect on p53 methylation. Serum level of DCST1-AS1 in AML children and healthy participants was detected by qRT-PCR. The role of DCST1-AS1 in mediating biological functions of AML193 and U937 cells was assessed by functional experiments. p53 methylation level was examined. Through BSP, MSP and dual-luciferase reporter assay, the regulatory effect of DCST1-AS1 on p53 methylation was explored. The correlation between DCST1-AS1 and p53 in the serum of AML children was assessed. Serum level of DCST1-AS1 was higher in AML children than in healthy subjects. Knockdown of DCST1-AS1 decreased proliferative and migratory rates in AML193 and U937 cells. DCST1-AS1 was able to induce methylation of p53 promoter. P53 was markedly upregulated by the knockdown of DCST1-AS1, presenting a negative correlation. LncRNA DCST1-AS1 drives the malignant progression of pediatric AML through inducing methylation of the p53 promoter.